A Possible case of complete loss of Vision after Intra Ocular Administration of Bevacizumab: Case Report - S, Sajida; S M, Jaffar; K, Balaji; G, Narayana (Indian Journal of Pharmacy Practice)
This is a case report focusing on a 62 years male patient who experienced complete loss of vision after the intra ocular administration of known strength of Bevacizumab. Bevacizumab is the choice of drug in the treatment of metastatic colorectal cancer, breast cancer, malignant mesothelioma, prostate cancer, age related macular degenerative and other ophthalmic diseases. But in this case Bevacizumab has developed severe adverse drug reaction which resulted in complete loss of vision. Naranjo's causality assessment algorithm was used to assess the adverse effect and it indicated Bevacizumab as probable cause of loss of vision.
Keywords: Bevacizumab; Vision loss; VEGF (Vascular Endothelial Growth Factor) Inhibitor; Monoclonal antibody